Reduced Expression of PLCXD3 Associates With Disruption of Glucose Sensing and Insulin Signaling in Pancreatic β-Cells - Aljaibeji, Hayat; Mukhopadhyay, Debasmita; Mohammed, Abdul Khader; Dhaiban, Sarah; Hachim, Mahmood Y.; Elemam, Noha M.; Sulaiman, Nabil; Salehi, Albert; Taneera, Jalal (Frontiers in Endocrinology, 2019)
Previous work has shown that reduced expression PLCXD3, a member of Phosphoinositide-specific phospholipases (PI-PLC) family, impaired insulin secretion with an unclear mechanism. In the current study, we aim to investigate the mechanism underlying this effect using human islets and in rat INS-1 (832/13) cells. Microarray and RNA sequencing data showed that PLCXD3 is among the highly expressed PI-PLCs in human islets and INS-1 (832/13) cells. Expression of PLCXD3 was reduced in human diabetic islets, correlated positively with Insulin, GLP1R expression and inversely with the donor’s body mass index (BMI) and glycated hemoglobin (HbA1c). Expression silencing of PLCXD3 in INS-1 (832/13) cells found to reduce glucose-stimulated insulin secretion (GSIS) and insulin content. In addition, the expression of Insulin, NEUROD1, GLUT2, GCK, INSRα, IRS2, and AKT were down-regulated. Cell viability and apoptosis rate were unaffected. In conclusion, our data suggest that low expression of PLCXD3 in pancreatic β-cells associates with down-regulation of the key insulin signalling and insulin biosynthesis genes as well as reduction in glucose sensing.